Design and Simulation of an Infinite Impulse Response Filter with Memristor - Ahmad Maleki; Vahid Rashtchi; Jalil Mazloum (Majlesi Journal of Electrical Engineering)
In this paper, a novel circuit for memristor based Infinite Impulse Response Filter (IIR) filter implementation is presented. In this research for increasing the input voltage range in sampling the analog signal, complementary switches were used instead of single-transistor switches. In addition, to increase the filter accuracy, a delayed circuit with the ability to implement high-order filters is presented. In this work, coefficients of the IIR filter were implemented by memristor; using such component could provide in-system reconfigurability. The memristor could decline receiving negative values, where IIR filter coefficients have negative values. In this research a new method for generating negative numbers as filter coefficients is presented. During running an advanced search algorithm, the memristor values ââwere set at six, seven, and eight bits of resolution; these values cause memristors have the lowest error rate in generating coefficients. All circuits were simulated by Cadence tools on TSMC 0.18 micrometer technology platform with 1.8 volt power supply. In simulation results, outputs of low/high-pass filters along with the error rate of coefficients calculated and compared to actual coefficients.